Data from: The skeletal taphonomy of anurans from the Eocene Geiseltal Konservat-Lagerstätte, Germany: insights into the controls on fossil anuran preservation - Falk, Daniel; Wings, Oliver; McNamara, Maria (Dryad, 2022)
The Geiseltal biota is a lacustrine-hosted Konservat-Lagerstätte from the
Eocene of central Germany. Despite its rich fauna and flora that is
represented by at least 50,000 fossil vertebrates, insects and other
invertebrates, plants and trace fossils, the taphonomy of the biota is
still poorly understood. In particular, the anurans have not been the
focus of taphonomic investigation. Here, we analysed the skeletal
taphonomy of 168 anurans from Geiseltal and scored each specimen for
orientation, completeness and articulation. Most specimens are partial
skeletons that were truncated during preparation. This process introduces
measurable artefacts into the taphonomic data and should be assessed in
future taphonomic studies on fossil vertebrates. The Geiseltal anurans
show several recurring taphonomic states, including disarticulation or
loss of abdominal bones, loss of one or more limbs, extensive
disarticulation and extensive loss of elements across the body. Relatively
rare taphonomic states include loss of distal limb elements only,
scattered bones and isolated, articulated limbs. These data are the basis
of a new taphonomic model for the Geiseltal anurans. Comparative analysis
of patterns in completeness and articulation in these specimens and in
fossil anurans from other Cenozoic Lagerstätten reveals repeated
taphonomic patterns in anuran preservation in lacustrine-hosted settings,
such as proximal to distal trends in completeness, preferential loss of
small peripheral bones, disarticulation of abdominal bones and
reorientation of major body regions and limbs. The taphonomic controls in
lacustrine systems are surface water temperature, lake depth, vegetation,
exposure to bottom currents, transport mechanisms, extent of scavenging,
decay regime, bone size and bone location in the skeleton. In turn, these
are ultimately controlled by palaeoclimate, lake physiography and
hydrology, and anuran anatomy. A universal approach to quantitative
analysis of skeletal taphonomy metrics will allow comparative testing of
the relationship between preservation and palaeoenvironment for diverse
fossil vertebrates.
Date of data collection: 02/2019–11/2020 Geographic location of data
collection: Natural Sciences Collections (ZNS), Halle (Saale), Germany.
SUPPLEMENTARY DATASET 1. Master dataset with skeletal taphonomic data for
the Geiseltal anurans. Data are shown for each of 140 specimens used in
the study and an additional 28 specimens that were excluded due to poor
preservation (precluding confident identification of individual skeletal
elements). Specimens lacking a full limb are identified on the basis of
the absence of at least one humerus or femur and their respective distal
limb elements. Specimens showing isolated limbs only are omitted from this
analysis; specimens are also omitted where truncation (i.e. of the torso)
prevents confidence of presence/absence of humeri and/or femura.
Abbreviations: Ce, ‘Cecilie’ pit; IL, ‘Geiselröhlitz’ site; GMH,
Geiseltalmuseum Halle; hyphen (-), unknown; indet., indetermined; Leo,
‘Leonhard’ pit; LMC, lower middle coal; LUC, lower upper coal; MC, middle
coal; MUC, middle upper coal; Nw, ‘Neumark-West’ pit; N/A, not applicable;
UHM, upper ‘Hauptmittel’ (‘Hauptmittel’: intercalated sandy and silty
successions); UMC, upper middle coal; XXXV, most likely Neumark-Süd pit
(NsXXXV). SUPPLEMENTARY DATASET 2. Completeness data. Completeness data
for each skeletal element in each specimen. Absence and presence of an
element represented by a single bone (e.g. left humerus) are coded ‘0’ and
‘1’, respectively. Completeness categories for multi-bone elements (e.g.
left phalanges) are defined in the main text and in the table column
header. Abbreviations: Ce, ‘Cecilie’ pit; IL, ‘Geiselröhlitz’ site; GMH,
Geiseltalmuseum Halle; hyphen (-), unknown; Leo, ‘Leonhard’ pit; Nw,
‘Neumark-West’ pit; N/A, not applicable (e.g. if the element in question
is distal to a truncated element); Trunc#, element truncated, but up to #
bones present; xx, not confident; XXXV, most likely Neumark-Süd pit
(NsXXXV). SUPPLEMENTARY DATASET 3. Articulation data. Articulation data
for each joint in each specimen. Disarticulation and articulation of a
single joint (e.g. left radioulna-humerus) are coded ‘0’ and ‘1’,
respectively. Articulation categories for multi-joint elements (e.g. left
phalanges) are defined in the main text and in the table column header.
Abbreviations: Ce, ‘Cecilie’ pit; IL, ‘Geiselröhlitz’ site; GMH,
Geiseltalmuseum Halle; hyphen (-), unknown; Leo, ‘Leonhard’ pit; Nw,
‘Neumark-West’ pit; N/A, not applicable (e.g. if the element in question
is distal to a truncated element); Trunc#, element truncated, but up to #
bones present; xx, not confident; XXXV, most likely Neumark-Süd pit
(NsXXXV).
Keywords: fossil amphibians; Konservat-Lagerstätten; Geiseltal; fossil preservation; FOS: Earth and related environmental sciences